Konsep AsbÄb Al-NuzÅ«l Menurut Nashr Hamid Abu Zayd - Munjin, Shidqy (MAGHZA, 2018)
This article aims to examine the concept of asbÄb al-nuzul which has been misunderstood by ulama and thus produces misleading conclusions. The results of this study indicate that Abu Zayds criticism of the established concept of asbÄb al-nuzÅ«l in the âulÅ«m Al-QurÄn was focused on the problem of the relation between the text and realities. According to him, the study of the first scholars was too focused on the Koran itself and the Prophets person as the recipient of revelation, but they forgot the community around the Prophet which was the most important element of reality that existed at that time. Whereas for Abu Zayd, the existence of asbÄb al-nuzÅ«l is strong evidence to show the relationship and dialectic between text and reality. To elaborate on his conception, Abu Zayd elaborated on four basic problems, namely regarding the reasons for the Al-Qurans a gradual descent, the gradual model of decline, the concept of DalÄllah in understanding a verse and its relation to asbÄb al-nuzÅ«l and finally on how to determine asbÄb al-nuzÅ«l.